Efficiency of an aquatubular boiler from the burning of four cultivars of sugar cane - Dias, Marcelo Costa (2020)
The growing demand for energy from renewable sources increasingly seeks to implement efficient energy production systems. Thus, the objective of this work is to determine the thermal efficiency of an aquatubular boiler that will burn the bagasse from four sugarcane cultivars: SP 80-1816, RB72-454, SP80-3280 and SP81-3250. This efficiency will be determined through the calculation methods: PCI - lower calorific value, PCS - higher calorific value and direct method. These cultivars were planted in the south-central region of Brazil where the largest sugar cane producers in the country are located. The results obtained show the importance of the energy analysis that each cultivar provides for energy cogeneration, as well as the benefits that will directly influence its production chain for controlled management. Among the benefits of controlled management are: maximizing processes and optimizing the energy use of each cultivar. The optimum efficiency of the boiler in energy production in relation to steam production depends on the intrinsic variables of each cultivar, such as bagasse and moisture content. When calculating the boiler efficiency, the SP 80-1816 variety proved to be more advantageous in relation to the others, considering the same characteristics of the production process, planting region, harvest time and the same type of boiler used. Still related to the study, the cultivar SP 80-1816 requires a smaller amount of bagasse in the boiler feed to produce heat, which results in greater energy production considering the same amount of bagasse of the studied varieties.